Analisis Pengaruh Digitalisasi Terhadap Kepuasan Kerja dan Implikasinya pada Kinerja Pegawai di Dinas Komunikasi dan Informatika Kabupaten Serdang Bedagai - M Dian Andika,; Andy Wijaya Hasibuan,; Cia Cai Cen,; Sarwoto, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of digitalization on job satisfaction and its implications for employee performance at the Communication and Informatics Office of Serdang Bedagai Regency. The sample in this study was 40 employees. The data analysis method used was the Structural Equation Model (SEM) based on Partial Least Squares (PLS). The analysis was conducted in three stages: the measurement model (outer model), the structural model (inner model), and hypothesis testing. The outer model was used to test the validity and reliability of indicators against latent variables. The inner model was used to examine the relationships between latent variables through the R² values. Hypothesis testing was conducted using a t-test to determine the significance of direct and indirect influences between variables. The results showed that digitalization significantly influenced job satisfaction and employee performance, but job satisfaction did not influence employee performance and was unable to mediate the relationship between digitalization and employee performance.